(untitled) - Dewhurst, Stephen C. (Upper Saddle River, N.J., 1995)
This is the long awaited second edition of the best-selling guide to Programming in C++. The authors discuss programming issues and develop topics of C++ programming paradigms and their supporting language features in parallel. Their goal is to foster understanding of C++ beyond simple syntax, so that it can be used as a flexible and effective programming tool. Interweaves a presentation of the C++ language features with discussion of the techniques and paradigms for which they were designed. Includes new information on key langauges features, such as templates, exception handling, and wide characters. For programmers familiar with C who are interested in programming in C++.
Keywords: C++ (Computer program language),Ngôn ngữ lập trình